Produção orgânica irrigada e rentabilidade do pimentão amarelo sob diferentes ambientes e dosagens de biofertilizante - Guimarães, José Wanderley Augusto (2013)
The use of biofertilizers in protected environments have been used to reduce the use of pesticides and protecting plants from pests and diseases , especially when weather conditions are adverse during the rainy season in the Northeast. Looking analyze these aspects , two surveys were conducted aiming to verify the behavior of the hybrid yellow peppers, irrigated and organic management under different environments and dosages of biofertilizers. In the first study treatments consisted of using three environments (greenhouse and open field trellis) and five doses of biofertilizer (0, 20, 40, 60 and 80 mL plant-1 week-1) applied through drip irrigation. It were observed temperature, relative humidity and incident solar radiation, and determined the following parameters of plant growth: Plant height, stem diameter, leaf area, average length and diameter, flesh thickness, total soluble solids and yield per plant. In the second study, measurements of other biofertilizer (0, 250, 500, 750 and 1000 mL plant-1 week-1), due to the financial analysis of the first study demonstrated RBC < 1.0 and negative NPV for all treatments were used in addition to low productivity. In addition to the determinations of the growth parameters and post-harvest of the first study, were determined in leaves the macronutrient (N, P, K, Ca, Mg and S). The climatic data were compared using linear regression and correlation coefficients. Growth variables, production and post-harvest were subjected to analysis of variance. When significant by F-test, the data regarding the types of environments (qualitative treatment) underwent test of means by Tukey test. Data regarding dosages of biofertilizer (subplot, quantitative) were subjected to regression analysis seeking to adjust equations with biological meanings. In the financial analysis were determined cash flow and profitability following indicators: cost benefit ratio, net present value, and internal rate of return and sensitivity analysis. According to the results, it was concluded: the dosages of biofertilizers adopted by producers of Sierra Ibiapaba are incipient to a first crop of peppers under organic management, the environment greenhouse is the most suitable for the cultivation of sweet pepper even with temperatures more high that the trellis and open fields, the organic cultivation of sweet pepper under biofertilizer doses of between 20 and 80 mL plant-1week-1 is financially unfeasible. The cultivation of sweet pepper in greenhouses with the higher dosage of biofertilizers proved to be the most efficient in most growth variables, production and post-harvest analyzed. The levels of nitrogen, potassium, magnesium and calcium were higher in the leaves of the greenhouse and trellis. On the other hand, the phosphorus content was higher in plants open, while the sulfur showed similar values for the three environments, in spite of a small decrease in the trellis plant environment. As for dosages of biofertilizer , it is found increasing linear trend with increasing dosages for contents of nitrogen, phosphorus , potassium and decreases in the level of calcium and magnesium , with increasing fertilizer. This decrease was also observed in the sulfur content, but a more sharply from 200 mL plant-1week-1. Organic cultivation of sweet pepper under proper Biofertilization is financially viable, especially in the greenhouse environment.